Concretizing occupational justice constructs in occupational therapy practice within the substance addiction rehabilitation setting in the Philippines. - Sy, Michael P.
This dissertation consists of five related studies that were collectively grounded on occupational justice, a concept that conjoins occupational science and occupational therapy. The overall aim of this dissertation is to explore the potentialities of integrating occupational justice principles within occupational therapy practice in Philippine-based SAR settings. As a result of the empirical studies conducted in the past two and a half years, the following conclusions were formed: 1) an analysis using the occupational science concepts of form, function, and meaning revealed that illicit drug use, to a certain extent, conforms to Filipino social norms, values, and moral standards. This is demonstrated by the desire of some Filipinos to gain agency, enhance productivity, and increase economic participation by using illicit drugs amid social inequalities and occupational injustices brought about by the intricacies of poverty; 2) Filipino occupational therapists working in SAR practice have a tripartite role: promoter of occupational participation; collaborators to enhance participation and well-being, and facilitators of environmental supporters for occupational participation. These roles are not mutually exclusive and may be performed all together to promote occupational participation during and even after rehabilitation. 3) a single-case study revealed how the Occupational Justice Health Questionnaire (OJHQ) is a practical tool that can be used by occupational therapists in several ways. Firstly, to identify injustices experienced by Filipino citizens who use(d) illicit drugs. Secondly, to prioritize what occupations can be used to promote occupational participation and justice. Lastly, to open potential collaboration with other professionals, community workers, and agencies in co-creating population-focused SAR programs. 4) Filipino citizens who use(d) illicit drugs follow a chronological pattern framed within four periods of participation: living with drugs, living around rules, and living for the future, and living amidst the war on drugs. Across four periods, injustices were uncovered that activated the first enablement skill, raise consciousness of occupational injustice from the Participatory Occupational Justice Framework. In this study, we found that while there were injustices experienced by the residents before entering the DTRC, these injustices were not totally eradicated but were replaced by new forms of injustices when they were residing in the DTRC. This primary finding asserted the position of occupational therapy in enhancing local SAR programs through the use of occupation-based social participation interventions, creation of partnerships and collaboration with other professionals and agencies, utilize a participatory approach in discussing and addressing injustices, and deliberate use of political activities of daily living. 5) an autoethnographic approach in analyzing researchers' field notes revealed an expanded purpose of the OJHQ including potentially enhancing practitioners' narrative clinical reasoning, enriching clinical data through non-clinical data extracted from the OJHQ, and integrating the documentation of social and justice determinants of health within the healthcare system.